Multicomponent seismology in petroleum exploration - Tatham, R. H. 1943- (Investigations in geophysics, 1991)
The book focuses on applications of multicomponent seismology with emphasis on interpretation. Preliminary discussions on the basic fundamentals stress an understanding of what additional information is available in multicomponent seismic data: in particular using P- and S-wave data allows estimations of lithology and fracture parameters. A discussion of laboratory observations develops some intuitive insight to assist in interpretation of multicomponent data, while acquisition and processing sections deal with those aspects that differ from conventional data acquisition and processing.